Geomorphic and Climatic Drivers Are Key Determinants of Structural Variability of Mangrove Forests along the Kenyan Coast - Njiru, Derrick Muthomi; Githaiga, Michael Njoroge; Nyaga, Justine Muhoro; Lang’at, Kipkorir Sigi; Kairo, James Gitundu (MDPI, 2022)
Mangrove forests occur across a diversity of coastal landforms that inﬂuence their structural development and productivity. Preliminary studies in Kenya indicate that mangroves growing in the region north and south of Tana River delta have different structural attributes. We hypothesise a close relationship between mangrove distribution, climate and landform types. Floristic composition of mangroves along the coast of Kenya was characterised and differences illustrated using non-metric multidimensional scaling (nMDS). Other structural properties of mangroves such as tree height, basal area, stand density and standing biomass were also assessed and their differences tested using analysis of variance (ANOVA). A hierarchical cluster analysis was used to compare mangrove species based on structural properties. Additionally, a regression ﬁt model was used to investigate the relationship between mangrove standing biomass and possible drivers of variability. The study revealed signiﬁcant differences in mangrove tree diameter, tree height, basal area, stand density and standing biomass across the sampled sites. High values of structural complexity were observed in estuarine and deltaic settings with high inﬂuence of freshwater input whereas low levels of structural complexity were observed for peri-urban with direct human inﬂuence. Our ﬁndings suggest that structural variability of mangroves in Kenya is highly inﬂuenced by geomorphological and climatic variability along the coast as well as the past and present management regimes of the forest.
Keywords: mangrove biogeography; forcing functions; biomass; complexity index; Kenya